Regulatory region of the gene for the ompA protein, a major outer membrane protein of Escherichia coli - Movva, N. Rao (1980)
The ompA protein, an outer membrane protein required for conjugation, is one of the most abundant proteins in Escherichia coli. The structural gene for the ompA protein cloned in a plasmid vector, pMF21, conferred sensitivity to ompA protein-specific phages. We have determined the DNA sequence of a fragment of 533 base pairs encompassing the regulatory region of the ompA gene: the promoter region, the 5′-untranslated region, and the region corresponding to the signal peptide for this secretory protein. The promoter region has a sequence that is remarkably homologous with the lac and gal promoters. Particularly, both the ompA and gal promoters have the same octanucleotide sequence, T-C-A-C-A-C-T-T, in their RNA polymerase recognition site, which has been shown to be involved in the binding of cyclic AMP receptor protein to the gal promoter. Analogous with the observations in the gal operon, a specific RNA transcript was produced only when glycerol, a DNA-destabilizing agent, was added to a cell-free system directed by a DNA fragment of the ompA gene. These data indicate that the ompA mRNA has an untranslated region at the 5′ end of about 140 nucleotides. In this region there are two additional initiation codons (II and III) besides the initiation codon (I) for the pro-ompA protein. AUG-III is located 30 bases upstream from AUG-I and accompanies a ribosome-binding site. Therefore, AUG-III is likely to begin the synthesis of a pentapeptide. The termination codon for the peptide overlaps with AUG-II, so that the ribosomes could reinitiate from AUG-II without being released from the mRNA. This reinitiation leads to the synthesis of a heptapeptide. The termination codon for this peptide also overlaps with AUG-I, which initiates the production of the pro-ompA protein. Because AUG-I also has an adjacent ribosome-binding site, the tandem repeat of initiation codons and ribosome-binding sites may be an important mechanism for facilitating the rate of initiation of translation. Extensive secondary structures exist in the 5′ end as well as in the coding region of the ompA mRNA, which may also play a role in the function of the mRNA.